Strategi Baznas Kota Banjar Baru Kalimantan Selatan dalam Mengentaskan Kemiskinan Melalui Zakat, Infaq, dan Shodaqoh - Sulastri; Sa’da Kamaliya, GT. (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2022)
This study aims to identify strategies for the utilization of Zakat, Infaq, and Alms (ZIS) in the National Amil Zakat Agency (BAZNAS) in Banjarbaru City and to find out the results of an analysis of the supporting and inhibiting factors in the distribution of Zakat, Infaq, and Shodaqoh (ZIS) in the Amil Zakat Agency (BAZNAS) Banjarbaru City and to find out how much influence the distribution of zakat, Infaq, and shodaqoh (ZIS) funds has on poverty alleviation at the National Amil Zakat Agency BAZNAS Banjarbaru City. The type of research used in this research is exploratory research. This research was conducted to investigate utilization strategies, analyze the supporting and inhibiting factors as well as the distribution of zakat, infak, and shodaqoh (ZIS) funds for poverty alleviation at the National Amil Zakat Agency BAZNAS Banjarbaru City by conducting in-depth interviews with the chairman and Banjarbaru City BAZNAS employees regarding the strategy of empowering Zakat, Infaq, and Alms (ZIS) in alleviating poverty in Banjarbaru City. In the study it was found that the Banjarbaru City BAZNAS had carried out poverty alleviation through distribution to those who deserved it, and ZIS funds were also not only consumptive but also productive by empowering ZIS funds through the Banjarbaru Prosperous Program.